Benefits Of Health Protocol And Covid-19 Vaccination For Indonesian People - Markus Amid; Marthen Mau; Yondi Yondi; Henni Somantik; Eliantri Putralin (LPPPIPublishing, 2022)
Maintaining health and immunity as well as the benefit of the life of the general public is a fixed price. Therefore, the Indonesian people need to improve the implementation of the Covid-19 health protocol and vaccination to prevent the spread of the coronavirus which results in the death of Indonesian citizens. This paper uses a qualitative method with a library research approach. This paper resulted in the application of health protocols as preventive measures, coronavirus vaccination as a complement to maintain body stability; and consume water and vitamin C because the human body really needs vitamin C to maintain immunity and body stability from coronavirus attacks. However, the most important thing for all mankind in the world and Indonesia is to draw closer to God Almighty because He is able to help, protect, preserve, protect, and free humans from the deadly Covid-19 attack.